Teacher Certification vs. Actual Performance: Unraveling the Controversy Over Professional Allowances and Their Impact on Teacher Productivity - Abdul Rohman; Siti Aimah (International Journal of Science and Environment (IJSE), 2026)
This study aims to analyze and reveal how professional allowances provided through the teacher certification program contribute to teachers’ actual teaching productivity at Darussalam Junior High School in Blokagung, Banyuwangi. This study employs a qualitative approach using a case study design to analyze the contribution of professional allowances to teachers’ teaching productivity at Darussalam Junior High School in Blokagung, Banyuwangi. The research was conducted in May 2026, involving four informants selected through purposive sampling, consisting of the principal, the vice principal for curriculum, and two certified teachers. Data were collected through observation, semi-structured interviews, and document analysis, then analyzed using the Miles, Huberman, and Saldaña interactive model through the stages of open coding, axial coding, and selective coding. Data credibility was ensured through source triangulation, methodological triangulation, and member checking. The results indicate that professional allowances can enhance teachers’ work motivation and sense of responsibility as professionals, but do not automatically increase teaching productivity. Learning productivity is more strongly influenced by teachers’ professional commitment, as reflected in their willingness to continue learning, innovate, and develop adaptive teaching strategies. This study emphasizes that the effectiveness of certification cannot be adequately measured solely by improvements in well-being or certificate ownership, but rather by teachers’ ability to actualize their competencies in teaching practice. These findings broaden the perspective on certification policy evaluation by positioning Teacher Professional Capital and Professional Commitment as the foundation for building a performance-based evaluation system aimed at continuously improving the quality of learning.